Vegetative growth, flowering and effective fructification of 'Jubileu' peach under different interstock lengths - Tomaz, Zeni Fonseca Pinto; Lima, Claúdia Simone Madruga; Gonçalves, Michel Aldrighi; Rufato, Leo; Rufato, Andrea De Rossi (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effects of different interstock lengths on the vigor of 'Jubileu' peach plants. Interstocks with 5, 10, 15 and 20-cm length, from the low-vigor cultivar Granada, were used. Vegetative growth, flowering and effective fructification were evaluated. The experiment was carried out from March-2007 to December-2008 at Pelotas, RS, Brazil. The vegetative growth of 'Jubileu' peach orchard was directly related to the interstock length. Increases in interstock length anticipate the onset of flowering and full anthesis. Vigor reduction induced by longer interstocks increases floral differentiation. Interstock with 20-cm length promotes the highest reduction in plant vigor, but also increases plant mortality. Therefore, the 10 and 15-cm interstocks are the most suitable for high-density orchards.